Midline and Flank Approaches for Spaying: A Comparative Study in Cats (Research in Agriculture Livestock and Fisheries, 2024)
The study was conducted to compare midline and flank approaches for spaying in cats. Cats were divided into two groups based on surgical approaches for spaying, Group A (Flank approach) and Group- B (Ventral midline approach). To evaluate the best approach for spaying, various parameters such as length of the surgical incision, the extent of haemorrhage, ease of location and exteriorization of ovaries and uterus, duration of surgery, postoperative complications, and time required for complete wound healing were recorded. In addition, the heart rate, respiration rate, and temperature were recorded before the operation and on different days after the operation. The physical parameters significantly (P